'This is my story, how I remember it': In-depth analysis of Dignity Therapy documents from a study of Dignity Therapy for people with early stage dementia. (July 2017) - Johnston, Bridget; Lawton, Sally; Pringle, Jan
Dementia is a progressive condition that impacts on individuals, families and care professionals. Maintaining quality of life through engagement with the person with dementia is an important part of their care. Dignity Therapy is an interactive, psychotherapeutic intervention that uses a trained dignity therapist to guide the person with dementia through an interview that then creates a written legacy called a generativity document. This can provide knowledge to inform care, as the condition progresses. Generativity documents were analysed using framework analysis. Main themes from the analysis were origin of values, essence and affirmation of self, forgiveness and resolution and existentialism / meaning of life . These themes provide evidence of the type, scope and contribution that information generated from Dignity Therapy can make to the care and support of people with dementia. They provide information about the values, self-identity and the people and events that have been important to them and influenced their lives.